Implementation of a medical student-run telemedicine program for medications for opioid use disorder during the COVID-19 pandemic - Marcus Castillo; Brianna Conte; Sam Hinkes; Megan Mathew; C. J. Na; Ainhoa Norindr; David P. Serota; David W. Forrest; Amar R. Deshpande; Tyler S. Bartholomew; Hansel E. Tookes (Harm Reduction Journal, 2020)
Abstract Objectives The COVID-19 pandemic led to the closure of the IDEA syringe services program medical student-run free clinic in Miami, Florida. In an effort to continue to serve the community of people who inject drugs and practice compassionate and non-judgmental care, the students transitioned the clinic to a model of TeleMOUD (medications for opioid use disorder). We describe development and implementation of a medical student-run telemedicine clinic through an academic medical center-operated syringe services program. Methods Students advertised TeleMOUD services at the syringe service program on social media and created an online sign-up form. They coordinated appointments and interviewed patients by phone or videoconference where they assessed patients for opioid use disorder. Supervising attending physicians also interviewed patients and prescribed buprenorphine when appropriate. Students assisted patients in obtaining medication from the pharmacy and provided support and guidance during home buprenorphine induction. Results Over the first 9 weeks in operation, 31 appointments were requested, and 22 initial telehealth appointments were completed by a team of students and attending physicians. Fifteen appointments were for MOUD and 7 for other health issues. All patients seeking MOUD were prescribed buprenorphine and 12/15 successfully picked up medications from the pharmacy. The mean time between appointment request and prescription pick-up was 9.5 days. Conclusions TeleMOUD is feasible and successful in providing people who inject drugs with low barrier access to life-saving MOUD during the COVID-19 pandemic. This model also provided medical students with experience treating addiction during a time when they were restricted from most clinical activities.